1996
DOI: 10.1038/383450a0
|View full text |Cite
|
Sign up to set email alerts
|

Activation of specific RXR heterodimers by an antagonist of RXR homodimers

Abstract: Retinoid X receptor (RXR) plays a central role in the regulation of many intracellular receptor signalling pathways and can mediate ligand-dependent transcription, acting as a homodimer or as a heterodimer. Here we identify an antagonist towards RXR homodimers which also functions as an agonist when RXR is paired as a heterodimer to specific partners, including peroxisome proliferator-activated receptor and retinoic acid receptor. This dimer-selective ligand confers differential interactions on the transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
158
2
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(169 citation statements)
references
References 28 publications
6
158
2
3
Order By: Relevance
“…At a 100 : 1 molar ratio relative to the two natural retinoids, the RXR antagonist CD3159 30 does not have any appreciable effect on the growth arrest induced by ATRA, whereas it inhibits by approximately 50% the anti-proliferative action of 9-cis RA ( Figure 3D). At both 10 : 1 and 100 : 1 molar ratio, CD3159 lowers by approximately 20% the induction of NBT-reducing activity caused by 9-cis RA, while exerting only marginal effects on the ATRA-dependent elevation of the same enzymatic activity ( Figure 3E).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At a 100 : 1 molar ratio relative to the two natural retinoids, the RXR antagonist CD3159 30 does not have any appreciable effect on the growth arrest induced by ATRA, whereas it inhibits by approximately 50% the anti-proliferative action of 9-cis RA ( Figure 3D). At both 10 : 1 and 100 : 1 molar ratio, CD3159 lowers by approximately 20% the induction of NBT-reducing activity caused by 9-cis RA, while exerting only marginal effects on the ATRA-dependent elevation of the same enzymatic activity ( Figure 3E).…”
Section: Resultsmentioning
confidence: 99%
“…The RARa agonist AM580, 10 the RARb agonist CD2019, 28 the RXR agonists CD2809 and CD2915, 29 the anti-AP1 retinoid CD2409, the pan-RAR reverse agonist CD3106 (AGN193109) 46 and the pan-RXR antagonist CD3159 (LG100754) 30 were synthesized by CIRDGalderma Research and Development (Sophia Antipolis, France). The pan-RAR agonist TTNPB 27 was a kind gift from Dr. Klaus (Hoffmann-la Roche, Basel, Switzerland).…”
Section: Chemicalsmentioning
confidence: 99%
“…AP-1 is a rather ubiquitous inflammatory transcription factor, and it is responsible for the regulation of a large number of genes, including MMP-3, which were unaffected by LG268 treatment. Previous studies characterizing LG268 (41)(42)(43) indicated that treatment with this rexinoid activates a limited number of RXR-containing NHR dimers, including RXR-RXR, RXR-farnesoid X receptor, RXR-liver X receptor, RXR-peroxisome proliferator-activated receptor ␣ [PPAR␣], and RXR-PPAR␥. In reviewing the literature, we found substantial data linking specific ligands for PPAR␥ to inhibition of MMP production and therapeutic activity in models of arthritis (44)(45)(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…Because PPAR␥ activity depends on heterodimerization with RXR␣, it is possible that modulation of PPAR␥ and degradation by R-etodolac is mediated by its binding to RXR␣. Antagonists of RXR homodimers are known to function as agonists of RXR͞PPAR␥ heterodimers (36,37).…”
Section: Discussionmentioning
confidence: 99%